Research on the use of calcium carbide residue from the acetylene gas manufacturing factory to produce non-calcined brick - Duong, Nguyen Anh; Anh, Phan Luu; Man, Tran Thi; Lan, Tran Thi (Vietnam Journal of Earth Sciences, 2020)
In Vietnam, calcium carbide residue (CCR) from the acetylene gas factories are not properly treated, causing serious environmental pollution. Based on mineral composition determined by XRD, calcium carbide residue consisted mainly of portlandite (70-72%), calcite (14-16%), hydrocalumite (6-8%), and chemical composition determined by XRF method composed of CaO (53.02%), LOI (39.72%). This calcium carbide residue can be used as a source of hydrated lime, mixed with fly ash, sand, and cement to produce non-calcined bricks and test results show that brick specimens achieved compressive strength 3.0-7.5 MPa, water absorption 12.3-17.5%, density 1.28-1.80kg/cm3. The test bricks satisfied Vietnamese standards for construction bricks.